2006
DOI: 10.1111/j.1525-1497.2006.00460.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary care clinicians treat patients with medically unexplained symptoms

Abstract: OBJECTIVE: There is no proven primary care treatment for patients with medically unexplained symptoms (MUS). We hypothesized that a long‐term, multidimensional intervention by primary care providers would improve MUS patients' mental health. DESIGN: Clinical trial. SETTING: HMO in Lansing, MI. PARTICIPANTS: Patients from 18 to 65 years old with 2 consecutive years of high utilization were identified as having MUS by a reliable chart rating procedure; 206 subjects were randomized and 200 completed the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
151
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(159 citation statements)
references
References 25 publications
4
151
0
4
Order By: Relevance
“…One other study examined the effect of training primary care clinicians to identify and treat somatization using a biopsychosocial model (Smith et al, 2006). This study involved the most intensive such training programs studied, one entailing 84 hours over 10 weeks.…”
Section: Integrating Cbt Into Primary Carementioning
confidence: 99%
See 1 more Smart Citation
“…One other study examined the effect of training primary care clinicians to identify and treat somatization using a biopsychosocial model (Smith et al, 2006). This study involved the most intensive such training programs studied, one entailing 84 hours over 10 weeks.…”
Section: Integrating Cbt Into Primary Carementioning
confidence: 99%
“…Patients who received treatment from these trained nurses reported modest improvements on self-report scales of mental health such as mood and energy and physical functioning. A post hoc analysis was interpreted by the study's investigators as suggesting improvements were attributable to more frequent and appropriate use of antidepressant medication among patients of nurses who received the training (Smith et al, 2006).…”
Section: Integrating Cbt Into Primary Carementioning
confidence: 99%
“…Only one study showed a positive outcome 184 and four reported no effect of training on patient outcomes. 99,145,162,173 Trials of collaborative care models reported benefits, 150,188 as did trials of different types of psychological therapy [cognitive-behavioural therapy (CBT, reflecting interviews)].…”
Section: Medically Unexplained Symptomsmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23] Providing physicians with management guidelines [24][25][26][27] and educational programs has also been found to be modestly effective. 28,29 However, much room remains for improving the care of somatizing and hypochondriacal patients for several reasons. 30 First, these tend to be chronic and treatment resistant problems that are maintained by psychological and psychosocial homeostasis.…”
Section: Introductionmentioning
confidence: 99%